Assistência humanizada e estrutura organizativa. A necessária interface: a experiência do grupo de trabalho de humanização em um hospital de Belo Horizonte - Jacqueline Saldanha Mendes da Costa (2004)
This work is the result of a study conducted in a public hospital, located in the city of Belo Horizonte, Minas Gerais, Brazil. It aimed at verifying how the relation/compatibility among the organizational structure of the hospital and the Humanization Workgroup (Grupo de Trabalho de Humanização) is developed, having as reference the configuration created by the Brazilian Humanization of Hospital Care Program (Programa Nacional de Humanização da Assistência Hospitalar), which was ratified, at a later time, by the Brazilian HumanizationPolicy, both initiatives were proposed by the Countrys Ministry of Health. The Ministry proposal had the aim of redeeming health care humanization. In the participating hospitals, the employees should form the Humanization Workgroups, which are preferably composedby leaderships that represent the diverse functional categories and hierarchical levels present in such organizations. The workgroups will have the incumbency of leading the Humanization Program/Policy inside the hospitals, a task that requires autonomy, freedom and responsibility. For that reason, besides the theoretical study, a case study was also conducted in the Hospital das Clínicas of the Federal University of Minas Gerais, using instruments such as data collection, semi-structured interviews, document analysis and observation. The collected data were treated in a descriptive way, having the qualitative approach as strategy. Itcould be observed that, nevertheless compatibility among the organizational structure and the Ministry of health existed; the Humanization Workgroup the Humanization Committee did not achieve significant progress towards the implementation of the Huma nization Program/Policy. The Committee narrowed its actions to the compilation of projects with humanizing actions that already existed in the hospitals, as well as to the implementation of more punctual actions, contributing make the theme HC/UFMG more pa tent. It could also beobserved that the Humanization Committee was not effectively incorporated to the hospitals organizational structure, which didnt show any changes derived from its insertion, acting in a non-contextual way. This can be seen through the non-existence of a systematized monitoringof the committees directive and managerial body. However, it was clear that the committee has its actions limited by the hospitals material, financial and human resources and, only the hospitals Board of Directors grants those assets.